Aerobic Training Attenuates Differences Between Black and White Adults in Left Ventricular–Vascular Coupling and Wasted Pressure Effort - João L. Marôco; Abbi D. Lane; Sushant M. Ranadive; Huimin Yan; Tracy Baynard; Bo Fernhall (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Black compared with White adults have a higher risk for left‐ventricular hypertrophy and heart failure possibly due to the early onset of alterations in ventricular–vascular coupling (ie, arterial [Ea] to ventricular elastance [Ees] ratio) and wasted pressure effort (Ew). Aerobic training preserves the coupling ratio (Ea/Ees) and attenuates Ew, but whether this applies to Black adults is unknown. We hypothesized that Black rather than White adults would have greater training‐induced improvements in the Ea/Ees and Ew. Methods and Results Fifty‐four young adults with normal blood pressure (Black=24 [58% female]; White=30 [47% female], mean=24 years; SD=5 years) completed an 8‐week aerobic training (3 times/week, 65%–85% peak oxygen uptake). Ea/Ees was estimated via echocardiography and scaled to body surface area, and the Ew was estimated from pulse contour analysis. Black adults had lower Ea/Ees (difference (d)=0.49 [95% CI, 0.14–0.84 mm Hg/mL], P=0.007) and higher Ew (d=1127 [95% CI, 104–2007 dyne cm−2 s], P=0.005). Both groups exhibited similar (race‐by‐training interaction, P=0.986) training‐induced reductions in scaled Ea (d=−0.11 [95% CI, −0.18 to −0.04 mm Hg/mL], P<0.001). Only in White adults, scaled Ees increased (dwhite=0.39 [95% CI, 0.11–0.32 mm Hg/mL], P=0.003) and Ea/Ees was reduced (dwhite=−0.16 [95% CI, −0.33 to −0.18 mm Hg/mL/m2], P<0.001). Conversely, only Black adults exhibited reductions in Ew after training (dblack=−699 [95% CI, −1209 to −189 dyne cm−2 s], P=0.008). Conclusions Aerobic training‐induced differential effects on Ea/Ees and Ew of White and Black young adults hold the potential to reduce racial disparities. This warrants confirmation in a larger sample. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT01024634.